Method for Calculating the Unbalanced Current in Ungrounded Double Wye C-Type Harmonic Filters - Sergio Arrieta Meza; Fernando Salinas Salinas; Luis Alonso Trujillo Guajardo; Luis Humberto Rodríguez Alfaro; Mario Alberto González Vázquez; Johnny Rodríguez Maldonado; Miguel Angel Platas-Garza (Energies)
This paper presents a methodology to calculate the neutral unbalanced current in C-type filters with an ungrounded double Wye topology; this equipment is widely used in the steel sector to mitigate the harmonic content in electrical installations caused by electric furnaces used in metal smelting processes. A common failure in these filters is the current unbalance caused by the degradation of the capacitor and inductor modules, leading to dangerous surges that affect these components, possible harmonic resonances, and deficient filtering by the equipment. Currently, there are no documented strategies for calculating the neutral current that allow for the proper adjustment of neutral protection in this type of equipment, resulting in catastrophic failures, costly unscheduled shutdowns, and potential harm to plant personnel. In this paper, we propose a methodology for calculating the unbalanced current in double Wye C-type harmonic filters, considering the natural degradation of capacitor and inductor modules and based on on-site measurements of the impedances for each element of the equipment. This allows for the predictive maintenance of these devices and the precise adjustment of neutral overcurrent protection. First, we review the operating principle of C-type harmonic filters and the neutral protection scheme. Then, the calculation methodology is proposed and validated in two practical case studies. In the first case, a 45 Mvar C-type second harmonic filter connected to a 34.5 kV bus is analyzed. In the second case, an 18.5 Mvar C-type second harmonic filter, part of a ±80 Mvar STATCOM system, connected to a 34.5 kV bus is examined. In both cases, these filters reduce the harmonic content in two steel plants: the first connected to a 400 kV bus and the second to a 230 kV bus. The results obtained with the proposed methodology were implemented in the protection device for a neutral current imbalance, considering different degradation values of the capacitors, and compared with the manufacturer’s suggested settings. The discussion highlights the good performance of the proposed methodology, particularly in terms of the protection device’s response speed to a risky unbalanced current.